Perbandingan Pengaruh Lampu UV dan Sinar Matahari Pada Degradasi Zat Warna Congo Red Menggunakan Metode Fotolisis Dengan Bantuan Katalis TiO2 - Julizen, Rofilian; Sanjaya, Hary (Periodic, 2023)
Research conducted by photolysis method to degrade Congo Red dye produced from textile industry waste that has a negative impact on the environment using a TiO2 catalyst aims to determine the optimal degradation percentage on the effect of radiation time and the effect of UV lamp power on the degradation of Congo Red. UV-VIS spectrophotometer measurement results obtained a wavelength of 497nm. The results showed that the percentage of degradation of the optimum radiation time was 92% at 180 minutes, and under the influence of UV lamp power the highest percentage of degradation was 95.21% at 20 watt UV lamp. This study showed that the hydroxyl radical (∙OH) was the main control in degrading Congo Red.